CSR, moral licensing and organizational misconduct: A conceptual review - Yassin Denis Bouzzine; Rainer Lueg (Organization Management Journal (OMJ), 2023)
Purpose - The purpose of this paper is to conceptualize how past corporate social responsibility (CSR) affects the occurrence of organizational misconduct by the means of moral licensing. Design/methodology/approach - To this end, the authors conduct a conceptual review and develop a framework illustrating how moral credits and moral credentials (moral licensing) may institutionalize irresponsibility and lead to subsequent misconduct. Findings - The authors propose a conceptual framework that describes the relationship between past CSR and organizational misconduct by the means of moral licensing. Based on initial literature-based findings, this paper provides confirmatory evidence for the authors' framework and illustrates that past CSR might be used as a moral licensing tool that eventually fosters the occurrence of organizational misconduct. Research limitations/implications - The authors propose future researchers account for the moral licensing effect when examining the antecedents of misconduct and explore the potential moderators of this effect. Practical implications - The authors recommend that organizations establish management control systems that specifically address the issue of moral licensing when evaluating CSR initiatives. The authors also propose that organizations should adhere to a consistent CSR strategy that potentially fosters the selection of moral leaders who are not prone to moral licensing. Originality/value - To the best of the authors' knowledge, this paper is the first to connect corporate social responsibility, moral licensing and organizational misconduct from a conceptual perspective.
Keywords: 650; CSR; Institutional theory; Management control; Moral licensing; Organizational misconduct